PROPOSED MARKETING STRATEGY FOR SUDIRMAN CENTRAL BUSINESS DISTRICT (SCB - Talitha Bashsha, Jyestha
The use of technology and the amount of interaction in social media has led a new form of competition between companies and its competitor. This situation is amplified with Covid-19 pandemic that change not only lifestyle, but particularly the way corporations operate its businesses. Consumer interactions become more and more borderless, exchange of information happens very quick and interactive to the point that makes them very dependent to virtual connectivity. However, some industries are hardly catching up with this technological demand. Real estate, as a part of property industry, has been functioning with a technological gap compared to other organizations that rely significantly on innovation and growth. Renters have sought a way to tour and manage properties online or with low-contact interaction. It is vital for the organization to stop running the business like classic real eastate, and start to move rapidly towards technological change so real estate corporations could thrive. One of market leaders in property industry in Jakarta is Sudirman Central Business District (SCBD). Based on CSI Report by Kantar (2019), internal CSI Report (2020) and the survey done for this research, respondents agree that SCBD is wellmaintained and has all the feature that makes it becomes the one-stop destinationiv for all needs. However, consumer could only experience SCBD when they present in the area. Eventhough SCBD has a strong brand, business landscape does not stop evolving. Since pandemic, companies have been asking whether keeping office space is still necessary or not; some big tech companies has operate remotely from anywhere without needing a space in an office tower to work. The current trend of a no to a minimum physical interaction should raise a deliberate attention about its marketing strategy to reach and stay relevant to its customer––that are now, most of them, are staying at home. A well-connected community and an era of sharing economy force companies to revisit its current strategy and its relevancy. In the case of SCBD, inclusivity is one of the defining variable that could connect the brand and its consumer. It suggests a better connectivity between SCBD and its potential tenants. A digital marketing with a focus on lead-generating marketing would also meet the inclusivity virtually, that would engage a lot more audience for SCBD, but also at once capturing interests and leads that contribute directly to the business. For the most part, inclusivity is proposed to complement SCBD’s well-known physical features by adding emotional aspects to the equation. Its comfortable, easy access and secured district would be more inviting for people to come and enjoy to stay in the area if SCBD reach out to its customer by stressing out the emotional features.